Zakat Fund Collection Optimization Strategy Based on Digital Technology: An Empirical Study in West Java - Jalaludin Al Mahali; Irfan Syauqi Beik; Ahmad Juwaini; Qurroh Ayuniyyah (Department of Public Administration, 2026)
Indonesia has enormous national zakat potential exceeding IDR 300 trillion; however, its realization remains very low, at only around 3.9%–5%. This gap has significant social implications, particularly in limiting the optimal distribution of zakat for poverty alleviation, social welfare improvement, and economic empowerment of vulnerable communities. This study aims to formulate a strategy for optimizing zakat collection in the West Java region by identifying and prioritizing the most influential determinant factors, particularly trust, technology adoption, and institutional capacity in digital zakat management. The study employs the Analytical Hierarchy Process (AHP) method involving seven experts through Focus Group Discussions (FGDs) and in-depth interviews. The results indicate that building communication and trust is the top strategic priority with the highest weight (0.368). Muzakki is identified as the most influential key actor across all decision factors. The managerial implications for Zakat Management Organizations (OPZ) highlight the need to strengthen a transparent digital ecosystem and collaborate with local figures to build social proof and enhance muzakki loyalty. In addition, digitalization should evolve beyond functioning merely as a payment channel into an integrated information ecosystem capable of providing real-time transparency reports to meet the expectations of digitally literate zakat payers. Strategic partnerships with fintech platforms, e-commerce, and community networks remain important as long-term reinforcement to expand outreach, particularly among digitally active younger generations.